Drought assessment in Tel River basin, Odisha using Standard Precipitation Index (SPI) - Ramesh Kumar Patel,; Narender Verma, (National Geographical Journal of India, 2023)
The present study attempts to assess drought in the Tel River basin, the second largest tributary of Mahanadi flowing through one of the most drought-frequented regions, viz. Nabarangpur, Kalahandi, Bolangir, Boudh, and Kandhamal districts of Odisha using Standard Precipitation Index (SPI). The SPI is one of the most widely used indices for monitoring drought based on rainfall data. It expresses the actual rainfall as a standardized departure concerning the rainfall probability distribution function. The values of SPI are expressed in standard deviations, with positive SPI indicating greater than median precipitation and negative values indicating less than median precipitation. A monthly time series climatic dataset is obtained from the NASA power data for 15 meteorological observation sites around the study basin from 1981 to 2021. The long-term data is then fitted to a probability distribution to create a normal distribution to find the cumulative probability of an observed precipitation event for the given month and time scale at the location in question. The cumulative probability H(x) is then converted to the conventional normal random variable z with a mean of zero and a variance of one yielding the SPI value. A drought event occurs when the index reaches -1.0 or below continuously. For three-time scale analysis of three months SPI 3, six months SPI 6, and twelve months SPI, DrinC software and Arc GIS 10.5 are used. The result shows that in the 40 years (1981-2021), 67 per cent of the droughts have been mild droughts, 18 per cent moderate droughts, 10 per cent severe droughts, and 5 per cent extreme droughts in the study basin. The regional distribution at the sub-basin level did not show any significant pattern based on the selected years of drought in the study basin.